Educação e extensão rural: um estudo dos diferentes métodos e técnicas utilizados pela Emater/RS - Santos, Nádia Potter dos (2006)
Educational questioning has always been closely associated with social, political and economic questioning as a whole. Beginning from the assumption that there is no neuter education, and that it always acts in the production or reproduction of a political ideology, it was tried an analysis of the several theories that underlies the different moments of educational practice in Rural Extension. The educative function has always permeated the practice of extension rural, that is the reason why this dissertation has the purpose to analyze the educative dimensions of Extension. With this in mind, it was decided to make a theoretical study of the different methods and techniques used in the educative work of the EMATER/RS, and an analysis of the advantages and limitation of methods and techniques used. The studies of George H. Axinn (1993) were used as a basis, where eight different extension approaches were identified all over the world. This research is justified because of the importance of the rural extension work in the country, especially in the State of Rio Grande do Sul, The used data collecting procedure employed was documental analysis. EMATER/RS has presented evident efforts to consider the multifaceted reality and the necessity of using a holistic view to face the demands and problems. Nevertheless, the author says that the agency still uses some orthodox methods when working with its audience. The participant work, where the communities wishes, necessities and knowledge a are heard and considered, the institution technical, still use some quite orthodox methods at the time of constructing new knowledge. The interdisciplinarity paradigm already orientates philosophy and proposals of the institution, having been made as a more and more necessary path int the understanding of the rural population different problems and realities in the state of Rio Grande do Sul.